DEVELOPMENT OF TEACHING MATERIALS USING A REALISTIC MATHEMATICS EDUCATION APPROACH IN A MULTIPLE INTELLIGENCES PERSPECTIVE OF ELEMENTARY SCHOOL STUDENTS - Murni, Sukma; Ruqoyyah, Siti (PrimaryEdu : Journal of Primary Education, 2020)
AbstractThe background of this research is that thinking skills and awareness of the importance of mathematics need to be taught and trained to students from an early age because in everyday life many things are related to thinking skills and awareness of the importance of mathematics. The purpose of this study was to determine the effectiveness of teaching materials using the RME approach in the perspective of elementary school students' multiple intelligences. The method used is descriptive qualitative research with the study population is all elementary schools in the city of Cimahi. The instruments used in this study were written tests, observation, and documentation which were carried out at the pretest and posttest stages. The results of the research achieved were an increase in thinking skills and awareness of elementary students in learning mathematics and the availability of teaching materials using the RME approach.Â Keywords: Realistic Mathematics Education, Multiple Intelligences, Mathematics Learning.